RESEP KOPI "NAOTO COFFEE" DALAM PERSPEKTIF PERLINDUNGAN RAHASIA DAGANG - NIM. A1011211173, DERA ELVANY RIYADI (Jurnal Fatwa Hukum, 2025)
ABSTRACTTrade secrets are a form of Intellectual Property Rights that grant exclusive rights to the owner of business information that has economic value. This study aims to identify the advantages of the "Naoto Coffee" recipe that qualify it for legal protection as a trade secret, as well as the steps taken by the owner to protect this information. The method used in this research is juridical-sociological, with a descriptive-analytical approach and qualitative analysis techniques. The results show that the coffee recipe meets the criteria of a trade secret, including confidentiality, economic value, and adequate protection, through measures such as Non-Disclosure Agreements with employees and controlling access to sensitive information. These steps have proven effective in preventing the leakage of confidential information. The author suggests that Naoto Coffee improve employee training on the importance of maintaining confidentiality, use technology to secure data, and limit access to sensitive information only to employees who need it. Additionally, confidentiality agreements with third parties involved in sourcing raw materials or distribution should be implemented, along with stronger physical security policies at the workplace. Regular evaluations of these policies will ensure that protection remains relevant to technological and organizational developments, enabling Naoto Coffee to safeguard its recipes and maintain a competitive edge.Keywords: Trade secrets, Intellectual Property Rights, Naoto Coffee, Recipe, Legal protectionABSTRAKRahasia dagang merupakan bentuk Hak Kekayaan Intelektual yang memberikan hak eksklusif kepada pemilik informasi bisnis yang memiliki nilai ekonomi. Penelitian ini bertujuan untuk mengidentifikasi keunggulan resep kopi "Naoto Coffee" yang memenuhi kriteria rahasia dagang, serta langkah-langkah yang diambil untuk melindunginya. Metode yang digunakan adalah yuridis sosiologis dengan pendekatan deskriptif analitis dan analisis kualitatif. Hasil penelitian menunjukkan bahwa resep kopi ini memenuhi syarat kerahasiaan, nilai ekonomi, dan perlindungan yang memadai, termasuk melalui perjanjian kerahasiaan dengan karyawan dan pengelolaan akses informasi. Langkah-langkah ini terbukti efektif mencegah kebocoran informasi. Penulis menyarankan Naoto Coffee untuk meningkatkan pelatihan karyawan tentang pentingnya menjaga kerahasiaan, menggunakan teknologi untuk pengamanan data, dan membatasi akses informasi hanya untuk karyawan yang membutuhkannya. Selain itu, perjanjian kerahasiaan dengan pihak ketiga dan peningkatan kebijakan keamanan fisik di tempat kerja juga perlu diterapkan. Evaluasi berkala terhadap kebijakan ini akan memastikan perlindungan tetap relevan dengan perkembangan teknologi dan organisasi, sehingga Naoto Coffee dapat menjaga kerahasiaan resep dan mempertahankan keunggulan kompetitif.Kata kunci: Rahasia dagang, Hak Kekayaan Intelektual, Naoto Coffee, Resep, Perlindungan hukum